Enhanced Hard Magnetic Performance for MnBi Green Powders - Nam, Nguyen Hoai; Anh, Vuong Kha; Tan, Le Nguyen Nhut; Nam, Pham Hong; Kim Oanh, Vuong Thi; Trung, Tran Bao; Tuan Minh, Le; Van Toan, Nguyen; Triet, Dang Minh; Khanh, Nguyen Van; Vuong, Nguyen Van; Xuan Truong, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 40 No 2DO - 10.25073/2588-1124/vnumap.4880, 2024)
Mn 5 5 Bi 45 melt - spun ribbons were prepared by using the melt-spinning technique followed by annealing in Ar/5%H 2 gas mixture. The in-situ formation of ferromagnetic phase (denoted as LTP) of MnBi was observed by the multi-section cycled Differential Scanning Calorimetry (DSC) method. It was found that, the optimal annealing temperature range for forming MnBi LTP is 250 – 280 o C. The prolonging annealing time increases the content of MnBi LTP leading to the increase of saturation magnetization M s but paid by the drop of the intrinsic coercivity i H c . The MnBi green powders were prepared by the Low Energy Ball Milling method (LEBM) in N 2 liquid.  The maximum energy product of MnBi green powders is estimated about 10.8 MGOe.